LEGAL PROTECTION FOR GRABFOOD DRIVERS AGAINST FICTITIOUS ORDERS AS DEFAULT ACTIONS: A CIVIL LAW PERSPECTIVE - Ngaisah, Siti; Setiawan, Andi (YURIS: Journal of Court and Justice, 2022)
The business world in Indonesia is growing rapidly along with the technology development, especially for the business that uses technology as a medium. One example is Grab application which provides GrabFood feature where all activities are conducted online including the payment method. However, with the financing through cash, there is one consequence of GrabFood transaction resulting in fictitious order which can be described as an act of default. In this research, the authors discuss the legality of GrabFood online transactions in terms of positive law in Indonesia and the regulation of legal protection for Grabfood drivers against fictitious orders in civil law as a harmed party due to default. In this research, the authors use Juridical-Normative Research method that the legal materials obtained are sourced from secondary legal materials, statutory approach and case approach. This research is using a descriptive analytical specification in answering the research problem. Based on the research result, PT. Grab Indonesia does not have repressive legal protection against the occurrence of fictitious orders which can be used as an action to provide legal protection to drivers who receive fictitious orders, and provide full compensation to Grab drivers who receive fictitious orders.